PENGARUH MODEL PENEMUAN TERBIMBING TERHADAP HASIL BELAJAR PADA MATERI PRISMA DAN LIMAS DI SMP NEGERI I TALAGA JAYA - Sri Lestari Mahmud; Abdul Djabar Mohidin; Nursiya Bito; Siti Zakiyah (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2021)
This research aims to look at the influence of guided discovery learning models on students' learning outcomes. The type of research used is experimental research. Sampling in this research was conducted by simple random sampling technique. Data collection was carried out using instruments in the form of observation sheets and tests of learning outcomes. The data obtained is then analyzed descriptively and inferentially. The results of the data analysis showed that the students’ learning outcomes taught by the guided discovery model are higher than students’ learning outcomes taught by conventional models, and the guided discovery model was effective in teaching material surface area and volume of upright and pyramid prisms.